Vehicle Side Diagnostics of S&C (Current Problems in Rail Vehicles, 2021)
Railway switches and crossings (S&C) are a problematic element of the infrastructure in terms of total maintenance costs compared to a normal track. The article therefore deals with the possibilities of condition monitoring of S&C by moving vehicles and with the design of an intelligent diagnostic system for S&C, which will be able to detect deterioration of technical condition and allow the infrastructure manager a gradual transition to the predictive maintenance. The facts mentioned above would not be possible without the development, assembly and testing of hardware and software solutions, supplemented by the development of intelligent algorithms that can evaluate the state of the S&C structure by measuring the dynamic response not only on the infrastructure but also on the railway vehicle. The sought solution will contribute to the S&C structure service life extending and life cycle costs reducing and therefore the safety and smoothness of railway traffic can be increased.
Keywords: switches and crossings; diagnostics; predictive maintenance; safety